Last Planner System and the Performance of Construction Projects - Maximillian Maria Surjo Dewantoro (Petra Christian University, 2019)
Scheduling serves as one of the critical aspects in the construction business and industrial activity. The last planner system has been used as one of the methods on the construction project. By applying the last planner system as a construction control method, the project can run on schedule, the cost does not exceed planning, and the quality of work on a project can be guaranteed. This research seeks a correlation between the last planner system and construction project performance. This research using a questionnaire method to find the project last planner system implementation and project performance. The data that answered by respondents are analyzed using SPSS program with Spearman ranking to find a correlation between the last planner system and construction project performance. The results show that there are eight very strong and significant relations between the last planner system implementation and project performance.